Red cell distribution width as a predictor of outcome in acute pancreatitis in Children (Mediscope, 2025)
Background: Acute pancreatitis is a commonly encountered emergency in children but it has always been tough to predict accurately which subset of patients will become systemically unwell. Simple prognostic markers, such as red cell distribution width (RDW). This study was done to assess the usefulness of this marker.Methods: This observational study was conducted from July 2018 to June 2020 at the Department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka. Thirty-one children with abdominal pain diagnosed with acute pancreatitis were included in the study.Results: The mean age of the pediatric patients was 11.19 (±3.45) years. The mean red cell distribution width was 14.99 (±2.96). RDW